P78 Physical Inactivity is Associated with Mid-Thigh Intramuscular Fat in Patients with COPD. (19th November 2012) - Maddocks, M; Shrikrishna, D; Vitoriano, S; Tanner, RJ; Natanek, SA; Hart, N; Kemp, PR; Moxham, J; Polkey, MI; Hopkinson, NS
Abstract : Introduction: Quadriceps muscle impairment is an important complication of COPD occurring in mild as well as more advanced disease 1 . This is driven by physical inactivity and can include muscle atrophy and/or a shift towards a less aerobic phenotype with reduced Type I fibre proportions and a reduction in capillarity and oxidative enzymes. 2 We hypothesised that physical inactivity in COPD patients would be associated with intramuscular fat and that this could potentially be a non-invasive and non-volitional marker of muscle quality. Methods: Mid-thigh cross-sectional area (MTCSA), percentage intramuscular fat and skeletal muscle attenuation (Hounsfield units [HU]) were assessed using computed tomography (CT) image analysis. Tissues were differentiated using standard attenuation ranges; fat: –190 to –30HU and skeletal muscle: –29 to 150HU Quadriceps isometric maximal voluntary contraction (QMVC) was measured using a strain gauge. Fat-free mass index (FFMI) and the impedance ratio (Z200/Z5) were determined by bioelectrical impedance analysis. Daily step count and physical activity level (PAL) were recorded over 6 days using a multisensory biaxial armband accelerometer (SenseWear, Bodymedia; Pittsburgh, US). Results: 69 patients (mean (SD), 65(8) years, FEV1 44(21)% predicted, 54% male) participated in the study. Mean (SD) daily step count was 4502 (3274) steps; physical activity level 1.4 (0.2); QMVC 25.2 (5.9) kg; FFMI 17.3 (2.3)kg/m2, MTCSA 178 (43)cm2. Using a stepwise regression model incorporating MTCSA, intramuscular fat, skeletal muscle attenuation, QMVC, and FFMI as independent variables, only skeletal muscle attenuation (HU) was retained as an independent correlate of daily step count (r=0.34, p=0.006). In a similar model, percentage intramuscular fat was the only independent predictor of physical activity level (r=0.37, p=0.002). The bioelectrical impedance ratio (Z200/Z5) was also associated with skeletal muscle attenuation (r=0.40, p<0.001) in this cohort. Conclusion: These data suggest that muscle "quality" assessed using CT is independently associated with daily physical activity and may therefore have potential as a biomarker in this area. Shrikrishna D et al. Quadriceps wasting and physical inactivity in patients with COPD. Eur Resp J 2012; doi: 10.1183/09031936.00170111. Shrikrishna D, Hopkinson NS. Chronic obstructive pulmonary disease: consequences beyond the lung. Clin Med 2012; 12:71–4.